2019
DOI: 10.1039/c9sm01958h
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based thermoplastic poly(butylene succinate-co-propylene succinate) copolyesters: effect of glycerol on thermal and mechanical properties

Abstract: The thermal and mechanical properties of the bio-based thermoplastic copolyesters can be controlled by adjusting the glycerol content and this allows the use of such copolyesters in medical support, and coating on 3D fabrics applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…2,5-furandicarboxylic acid is a popular bio-based aromatic diacid monomer consisting of a furan ring to replace the terephthalate acid, achieving an excellent gas barrier property [19][20][21][22][23]. Otherwise, the cross-linking modifiers are frequently undertaken to improve the thermal and mechanical properties of bio-based copolyesters [24][25][26][27]. By doing so, the bio-based aliphatic polyester can be formed a partial cross-linking network architecture by a small amount of multi-arm cross-linking modifiers, such as benzene-1,3,5-tricarboxylic acid and glycerol with the tri-arms; 2,2-bis (hydroxymethyl) 1,3-propanediol, ethylenediaminetetraacetic acid and 1,2,4,5-benzenetetracarboxylic acid with the tetra-arms; cyclohexane-1,2,3,4,5,6-hexacarboxylic acid and hexahydroxycyclohexane with the hexa-arms, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5-furandicarboxylic acid is a popular bio-based aromatic diacid monomer consisting of a furan ring to replace the terephthalate acid, achieving an excellent gas barrier property [19][20][21][22][23]. Otherwise, the cross-linking modifiers are frequently undertaken to improve the thermal and mechanical properties of bio-based copolyesters [24][25][26][27]. By doing so, the bio-based aliphatic polyester can be formed a partial cross-linking network architecture by a small amount of multi-arm cross-linking modifiers, such as benzene-1,3,5-tricarboxylic acid and glycerol with the tri-arms; 2,2-bis (hydroxymethyl) 1,3-propanediol, ethylenediaminetetraacetic acid and 1,2,4,5-benzenetetracarboxylic acid with the tetra-arms; cyclohexane-1,2,3,4,5,6-hexacarboxylic acid and hexahydroxycyclohexane with the hexa-arms, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al have been synthesized the poly (ethylene sebacate-co-ethylene adipate) (PESA) with benzene-1,3,5-tricarboxylic acid, indicating a high Young's modulus from 140 to 200 MPa with varying adipate content due to partial cross-linking network created by the trimesic acid unit [24,25]. Hsu and coworkers developed a fully bio-based poly (butylene succinate-co-propylene succinate) (PBSPS) system with glycerol adjust the thermal-mechanical properties, revealing the PBSPS copolyesters could be transformed from elastic to rigid characteristics by increasing the glycerol concentration, and the elongation decreased from 800% to 20% [26]. Furthermore, Chen and colleagues developed a novel unsaturated aliphatic copolyester like poly (butylene adipate-co-butylene itaconate) (PBABI), which copolymerized with ethylenediaminetetraacetic acid (EDTA) to enhance the physical property, showing the cross-linking modifiers were the best choice to form the steric network structure to improve the mechanical and thermal properties of these kinds of aliphatic copolyesters [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The modifier can be selected with a multi arms end group with –OH and –COOH residues utilized in copolyesters; e.g., benzene-1,3,5-tricarboxylic acid and glycerol with the tri-arm; 2,2-bis(hydroxymethyl) 1,3-propanediol, ethylenediaminetetraacetic acid, and 1,2,4,5-benzenetetracarboxylic acid with the tetra-arm; cyclohexane-1,2,3,4,5,6-hexacarboxylic acid and 1,2,3,4,5,6-cyclohexanehexol with the hexa-arm. A slight content (0.01–0.3 mole%) of multifunctional end groups on aliphatic copolyesters has been explored to form a partial networking architecture, for which the thermal and mechanical properties were accurately regulated, while still maintaining the thermoplastic’s properties and easy processability [ 6 , 7 , 8 , 9 ]. For tri-arm modifiers, Chan and coworkers produced the poly(ethylene sebacate- co -ethylene adipate) (PESA) with benzene-1,3,5-tricarboxylic acid, observing a lower melting point in the rane of 60–70 °C, a relative higher Young’s modulus in a range of 140–200 MPa, and elongation in 35–75% due to a partial crosslinking network generated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For tri-arm modifiers, Chan and coworkers produced the poly(ethylene sebacate- co -ethylene adipate) (PESA) with benzene-1,3,5-tricarboxylic acid, observing a lower melting point in the rane of 60–70 °C, a relative higher Young’s modulus in a range of 140–200 MPa, and elongation in 35–75% due to a partial crosslinking network generated [ 6 ]. Hsu et al developed a fully biobased poly(butylene succinate- co -propylene succinate) (PBSPS) system with glycerol adjust the thermal-mechanical properties, revealing the PBSPS copolyesters could be changed from elastic to rigid characteristics by increasing the PS unit, proposing that the elongation decreased from 800% to 20% and Young’s modulus ranged from 288.19–58.11 MPa [ 7 ]. Furthermore, for tetra-arm modifiers, Chen and colleagues developed unsaturated poly(butylene adipate- co -butylene itaconate) (PBABI) copolyester, which copolymerized with ethylenediaminetetraacetic acid (EDTA) [ 8 ] and 1,2,4,5-benzenetetracarboxylic acid (BTCA) [ 9 ] to adjust the thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the PBI films produced in this study showed higher tensile strength values than those of conventional aliphatic bioplastics, such as poly(butylenesuccinate) (34 MPa), poly(3‐hydroxybutyrate) (40 MPa), PLA (60 MPa), and they were comparable with those of the available aromatic bioplastics such as polyimide, polyesters. [ 57–60 ] The processability of PBI into films is very important for its application in manufacturing, from plastics or matrices to composites with metals with high melting temperatures. The molecular rigidity of the fibrous materials of conventional high‐performance polymers is too high for their processing into films.…”
Section: Resultsmentioning
confidence: 99%